Applying Clinical Reasoning to Medical Records. A Different Point of View - Ariel Efrén Uriarte Méndez; Edwis Pérez Pintado; Yagén María Pomares Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
There have been serious deficiencies in the completion of medical records over the years, being the diagnostic discussion the section with more difficulties. This paper analyses such deficiencies, responsible for the lack of the most basic features and functions of medical records. It tries to get to the source of the poor quality of diagnostic discussions, while proposing a different approach that could solve the problem. We conclude that the problem is related to the unconditional requirement of a rigid structure, not applicable to all situations, which causes the adherence to this structure to affect the logical clinical reasoning.